FTIR imaging in diffusion studies: CO2 and H2O in a synthetic sector-zoned beryl - Della Ventura, Giancarlo; Radica, Francesco; Bellatreccia, Fabio; Cavallo, Andrea; Cinque, Gianfelice; Behrens, Harald (Frontiers in Earth Science, 2015)
In this work we investigate the strongly inhomogeneous distribution of CO2 and H2O in a synthetic beryl having a peculiar hourglass zoning of Cr due to the crystal growth. The sample was treated at 800°C, 500 MPa, in a CO2-rich atmosphere. High-resolution FESEM images revealed that the hourglass boundary is not correlated to physical discontinuities, at least at the scale of tens of nanometers. Polarized FPA-FTIR imaging, on the other side, revealed that the chemical zoning acts as a fast pathway for carbon dioxide diffusion, a feature never observed so far in minerals. The hourglass zone boundary may be thus considered as a structural defect possibly due to the mismatch induced by the different growth rates of each sector. High-resolution synchrotron-light FTIR imaging, in addition, also allows enhancement of CO2 diffusion along the hourglass boundary to be distinguished from diffusion along fractures in the grain. Therefore, FTIR imaging provides evidence that different diffusion mechanisms may locally combine, suggesting that the distribution of the target molecules needs to be be carefully characterized in experimental studies. This piece of information is mandatory when the study is aimed at extracting diffusion coefficients from analytical profiles. Combination of TOF-SIMS and FPA data shows a significant depletion of type II H2O along the hourglass boundary, indicating that water diffusion could be controlled by the distribution of alkali cations within channels, coupled to a plug effect of CO2.